2021
DOI: 10.1186/s12891-021-04647-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ risk factors for periprosthetic joint infection in primary total hip arthroplasty: a meta-analysis of 40 studies

Abstract: Background Periprosthetic joint infection (PJI) is a catastrophic complication after total hip arthroplasty (THA). Our meta-analysis aimed to identify the individual-related risk factors that predispose patients to PJI following primary THA. Methods Comprehensive literature retrieval from Pubmed, Web of Science, and the Cochrane Library was performed from inception to Feb 20th, 2021. Patient-related risk factors were compared as per the modifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 79 publications
2
34
0
3
Order By: Relevance
“…Prior studies, mostly meta-analyses, have identified obesity, smoking, rheumatologic disease, and diabetes as potential risks factors for infection [5,22,28,31]. In our study, smoking, body mass index ≥30, and rheumatologic disease were significantly more common among patients <75 years of age.…”
Section: Discussionsupporting
confidence: 48%
“…Prior studies, mostly meta-analyses, have identified obesity, smoking, rheumatologic disease, and diabetes as potential risks factors for infection [5,22,28,31]. In our study, smoking, body mass index ≥30, and rheumatologic disease were significantly more common among patients <75 years of age.…”
Section: Discussionsupporting
confidence: 48%
“…Так, ЦД є одним із факторів ризику розвитку перипротезної інфекції у пацієнтів при первинному тотальному ЕККС [12,13]. Встановлено, що передопераційна гіпоальбумінемія (альбумін <35 г/л), ожиріння (ІМТ ≥40 кг/м 2 ), тютюнопаління і ЦД підвищують ризик післяопераційної інфекції, повторної госпіталізації, будь-яких ускладнень та смертності після тотального ендопротезування кульшового суглоба [14].…”
Section: The Role Of Dexmedetomidine In the Structure Of Anesthesia F...unclassified
“…У 2 пацієнтів груп реґіонарної анестезії (у 2-й і 3-й по одному хворому -6,66%) на фоні початку анестезії і початку операції спостерігалася короткочасна гіпотензія зі зниженням САТ на 20-25 мм рт.ст. (15,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) Як свідчить аналіз табл. 2, після проведення анестезії у групах побічні ефекти розвивалися не часто і були порівнянні між групами, за винятком частоти виникнення нудоти й блювання і, відповідно, застосування антиеметичних засобів.…”
Section: результати дослідження та їх обговоренняunclassified
“…However, it is questionable whether these factors are true confounders, because they also relate to selected exposure. Lastly, we did not consider the body mass index (BMI) of patients, despite BMI being a significant risk factor for PJI (32). It is possible that BMI is a confounder if the dose and duration of thromboprophylaxis is modified in patients with high BMI.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%